SPIRITUAL FOREST OF PHUTAI PEOPLE: THE BIODIVERSITY OF SACRED PLANT AND ECOLOGICAL-CULTURAL VALUES IN SAKHON NAKHON BASIN, THAILAND - Tunwa Chaitieng; Thares Srisatit (European Scientific Journal, ESJ, 2013)
Phutai People are an indigenous tribe in the Lower Mekhong Basin and their history and culture are in terms of biological resource conservation. This research aims to study their ecological knowledge and formation of Spiritual Forest; and to study plants’ community characteristics, diversity and biological values in their society. This research integrates forest ecology with indigenous ecology, surveying social characteristics and biodiversity, which is then applied to qualitative research procedure through observation and in-depth interview of key informants to analyse ecological knowledge and plants’ values during field study at a Phutai village in Sakhon Nakhon province, Thailand from June 2011 to June 2012. The findings: Phutai people like living on the plains near mountains using simple production method, depending on nature with the growing of rice as their main occupation. They have traditional knowledge, important to spiritual dimensions: man, spirit and nature which are all interrelated and inseparable. When settling down, they also choose a nearby forest for village ghost (spirit) or god (Deva)’ s living place to oversee and protect the village. The forest is well taken care of and becomes a Spiritual Forest to conserve biological resources and native plant diversity. There are 95 Spiritual Forest in Phutai communities. These forests once serves as: an important source of biodiversity and native plants in Sakhon Nakhon Basin, a source of food and herb to support the Phutai people’s economy and ecology, a spiritual centre, and a foundation to create strength to maintain their idealism and traditional ecological heritage in the region.